Pelatihan Pengembangan Kemampuan Komunikasi Interpersonal Peserta Didik Di Rumah Tahfiz Qur’an (RTQ) Mushola Nurul Iman Kelurahan Penaraga Kecamatan Raba Kota Bima - Hermanto, Lubis; Rosadi, Ariani; Junaidin, Junaidin; Irham, Irham; Mas’ud, Mas’ud; Syamsuddin, Syamsuddin (CV. ITTC INDONESIA, 2023)
Interpersonal communication suggests that communication is important for building self-concept, for survival, self-actualization, for obtaining happiness, avoiding pressure and dependency, among others through entertaining communication, and fostering relationships with other people. Through interpersonal communication we can work together with community members to achieve common goals. Through communication with other people, we can fulfill our emotional and intellectual needs, by cultivating warm relationships with those around us. Interpersonal communication indicates that communication is done for self-fulfillment, to feel entertained, comfortable and at ease with oneself and also others. The methods used include varied lectures, demonstrations, and exercises. The results of this training will benefit students and youth, so that the communication delivered is better and has a clear meaning, which is easily understood by the other person. The process of learning and teaching in training activities will be more interesting by understanding the concepts and knowledge conveyed by professional lecturers in their fields. Besides that, with training activities for developing interpersonal communication skills, it is hoped that it will increase students' knowledge, especially communication science so that students can maximize their potential, develop their public speaking and be able to communicate well.